2020
DOI: 10.1096/fj.201902327r
|View full text |Cite
|
Sign up to set email alerts
|

Exercise as a countermeasure for latent viral reactivation during long duration space flight

Abstract: Latent viral reactivation is a commonly reported manifestation of immune system dysregulation during spaceflight. As physical fitness and exercise training have been shown to benefit multiple arms of the immune system, we hypothesized that higher levels of preflight physical fitness and/or maintaining fitness during a mission would protect astronauts from latent viral reactivation. Standardized tests of maximal strength, muscular endurance, flexibility, and cardiorespiratory fitness (CRF) were performed in 22 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 37 publications
(117 reference statements)
1
15
0
2
Order By: Relevance
“…Physically active individuals also exert better control over their latent viral infections, even during periods of isolation and confinement. For instance, recent work from our laboratory demonstrated that astronauts with increased levels of cardiorespiratory fitness and skeletal muscle endurance were ~40% less likely to reactivate a latent herpesvirus during a 6-month mission to the International Space Station (ISS), particularly if they were able to maintain their fitness levels on the ISS (Agha et al, 2020). Even in astronauts who did reactivate a virus, copies of viral DNA were fewer in the fitter astronauts indicating that they were less contagious than their less-fit counterparts.…”
Section: Viewpointmentioning
confidence: 99%
“…Physically active individuals also exert better control over their latent viral infections, even during periods of isolation and confinement. For instance, recent work from our laboratory demonstrated that astronauts with increased levels of cardiorespiratory fitness and skeletal muscle endurance were ~40% less likely to reactivate a latent herpesvirus during a 6-month mission to the International Space Station (ISS), particularly if they were able to maintain their fitness levels on the ISS (Agha et al, 2020). Even in astronauts who did reactivate a virus, copies of viral DNA were fewer in the fitter astronauts indicating that they were less contagious than their less-fit counterparts.…”
Section: Viewpointmentioning
confidence: 99%
“…Exercise in general can mitigate the negative effects of stress to maintain immune function, particularly during prolonged periods of isolation and confinement. It has been shown that astronauts in space travel for nearly 6 months with extreme isolation who had a higher pre-flight cardiorespiratory fitness and muscle endurance had a better immune response compared to astronauts who were not fit [22].…”
Section: Mental Health Social Isolation Anxiety and Increased Disease Risksmentioning
confidence: 99%
“…A transient exercise-induced immunosuppression described above may result in a transient post-exercise "open-window" of diminished ability to combat an infection, and during that period some situations representing an increased risk (i.e., going to supermarket) should be avoided. Nevertheless, in times as these of a pandemic and social isolation, it is important to avoid deconditioning as it will weaken the immune function and diminish the defense against viral infections (Agha et al, 2020). So, protect yourself, be healthy and keep exercising at moderate intensity for your health.…”
Section: Physical Fitness Lifestyle and Daily Recommendationsmentioning
confidence: 99%